Enhancement of work engagement through HRIS adoption mediated by workplace well-being - A. Ammupriya; Subrahmanyan, Preetha (Brazilian Journal of Operations & Production Management, 2023)
Goal: The purpose of this paper is to find out the Role of HRIS adoption in enhancing work engagement by considering the mediating effect of workplace well-being. Design/Methodology/Approach: Applying AMOS software, the (CFA) method is used to construct the actual SEM model. A well-structured questionnaire was framed and collected a maximum of 300 data points using a 5-point Likert scale in a non-probability convenience sample in several organizations. Results: SEM modeling has various constraints to evaluate the original and modification indices. It is found that there is a mediating effect on workplace well-being between the human resource information system and work engagement. The model establishes the significant impact of workplace well-being in organizations. Limitations of the investigation: Future research should address that HRIS adoption is necessary for every organization for better decision-making, but they will face challenges in adopting the HRIS Practical Implications: Receiving innovation in the working environment and recommending how it should be swiftly involved and transformed into a standard method of practice. Originality/ Value: The study demonstrates the originality and significance of the current model in developing the human resource information system, which helps to ensure employees’ workplace well-being towards the organization.